Analisis Propeller Yang Tidak Balance pada Kapal Tugboat Anugerah 1 - Apriyanto, Ricky; Darmana, Eka; Wilastari, Santhi (Universitas Ivet, 2023)
The case study on the tugboat award 1 experienced problems with the propeller which made it possible to be out of balance. The purpose of this research is to find out the causes of unbalanced propellers on ships and how to overcome them. The use of research methods using observation, interviews and data analysis by observing, reviewing and analyzing objects or problems that will be examined directly so that the data obtained is objective because the author experienced it himself and was at the ship docking location when the work of the propeller was not perfect. From the data obtained, then an analysis of descriptive qualitative methods was carried out. The results of this study state that the unbalanced propeller is caused by fouling, erosion, cracks, and deformation of the propeller blades. Possible triggering factors include long absence of maintenance, old components, and negligence in operation. An unbalanced propeller if not handled immediately is feared to cause damage to other components such as damage to the stern tube which results in leaks and can endanger the ship.